Inquiry-Based Student Worksheet Design for Introduction to Mathematical Statistics Course - Rezky Ramadhona; Sukma Adi Perdana (Universitas Maritim Raja Ali Haji, 2022)
In the new normal, learning is carried out online. For this reason, educators must be able to package the learning activity interactively so that students have the motivation to learn. The inquiry method facilitates students to be active in learning. Students are guided through the questions arranged in the Worksheet. Therefore, this study aims to develop an Inquiry-Based Student Worksheet in the Introduction to Mathematical Statistics in the New Normal Era. The development model used is 4D with the stages of define, design, develop, and disseminate. However, the stages of this article are defined and designed. The instrument used in the define stage is a questionnaire. The results at the define stage are that teaching materials are needed to help students find concepts, and the Student Worksheets are one of the teaching materials that have a good impact on learning.